Nurses’ Compliance with Elimination Care and Urinary Tract Infection Risk in Bedridden Patients - Dewi Nurhanifah; Wahidah; Uni Afriyanti; Lukman Harun (The Indonesian Institute of Science and Technology Research, 2026)
Urinary tract infection (UTI) is one of the most common healthcare-associated infections among bedridden patients using urinary catheters. Proper fulfillment of elimination needs by nurses is considered essential for preventing catheter-associated infections; however, evidence on its relationship to UTI risk remains limited. This study aimed to examine the association between nurses’ compliance with elimination care standard operating procedures (SOPs) and the risk of UTI among bedridden patients. A quantitative study with a cross-sectional design was conducted in an inpatient hospital setting involving 59 nurses and 59 bedridden, catheterized patients. Total sampling was applied to recruit participants. Nurses’ compliance with elimination care SOPs was measured using a validated questionnaire, while UTI risk among patients was assessed using a clinical observation checklist. Data were analyzed through univariate analysis and Fisher’s Exact Test with a significance level of α = 0.05. The findings showed that most nurses demonstrated very high compliance with elimination care SOPs. The majority of patients were categorized as having no UTI risk, while a smaller proportion showed potential risk. Statistical analysis indicated a significant association between nurse compliance and UTI risk (p = 0.028). Patients treated by nurses with higher compliance were less likely to experience UTI risk. These findings emphasize the importance of strengthening nurse compliance through continuous training, supervision, and monitoring to improve patient safety and nursing care quality.